A : 6x²+7x-3>0
B : 6x² + 7x - 3 < 0
C : 3-2x-x²>0
D : 3-2x-x²<0
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a: x+1>0
=>x>-1
b: -2x-3<0
=>-2x<3
=>x>-3/2
c: 4x+5>0
=>4x>-5
=>x>-5/4
d: -7x-3<0
=>-7x<3
=>x>-3/7
k: 3x+7>0
=>3x>-7
=>x>-7/3
l: -4x-1<0
=>-4x<1
=>x>-1/4
1. \(\Leftrightarrow\left(2x-1\right)\left(3x+1\right)< 0\)
\(\Rightarrow-\frac{1}{3}< x< \frac{1}{2}\)
2. \(\Leftrightarrow\left(x-2\right)\left(3-2x\right)>0\)
\(\Rightarrow\frac{3}{2}< x< 2\)
3. \(\Leftrightarrow\left(5x-3\right)^2>0\)
\(\Rightarrow x\ne\frac{3}{5}\)
4. \(\Leftrightarrow-3\left(x-\frac{1}{6}\right)-\frac{59}{12}< 0\)
\(\Rightarrow x\in R\)
5. \(\Leftrightarrow2\left(x-1\right)^2+5\ge0\)
\(\Rightarrow x\in R\)
6. \(\Leftrightarrow\left(x+2\right)\left(8x+7\right)\le0\)
\(\Rightarrow-2\le x\le-\frac{7}{8}\)
7.
\(\Leftrightarrow\left(x-1\right)^2+2>0\)
\(\Rightarrow x\in R\)
8. \(\Leftrightarrow\left(3x-2\right)\left(2x+1\right)\ge0\)
\(\Rightarrow\left[{}\begin{matrix}x\le-\frac{1}{2}\\x\ge\frac{2}{3}\end{matrix}\right.\)
9. \(\Leftrightarrow\frac{1}{3}\left(x+3\right)\left(x+6\right)< 0\)
\(\Rightarrow-6< x< -3\)
10. \(\Leftrightarrow x^2-6x+9>0\)
\(\Leftrightarrow\left(x-3\right)^2>0\)
\(\Rightarrow x\ne3\)
a) 2x + 5 < 0 => 2x < - 5 => x < -2,5
b) -4 - 5x > 0 => -4 > 5x => -0,8 > x
c) -7x + 3 < 0 => -7x < -3 => x > 3/7
d) x - 7 > 0 => x > 7
e) -3 + 4x > 0 => 4x > 3 => x > 0,75
\(a,2x+5< 0\) \(b,-4-5x>0\)
\(\Rightarrow2x< -5\) \(\Rightarrow-4>5x\)
\(\Rightarrow x< -\frac{5}{2}\) \(\Rightarrow x< -\frac{4}{5}\)
\(c,-7x+3< 0\) \(d,x-7>0\)
\(\Rightarrow-7x< -3\) \(\Rightarrow x>7\)
\(\Rightarrow x>\frac{3}{7}\)
\(e,-3+4x>0\)
\(\Rightarrow4x>3\)
\(\Rightarrow x>\frac{3}{4}\)
Bài 1.
a) ( 7x - 3 )2 - 5x( 9x + 2 ) - 4x2 = 18
<=> 49x2 - 42x + 9 - 45x2 - 10x - 4x2 = 18
<=> -52x + 9 = 18
<=> -52x = 9
<=> x = -9/52
b) ( x - 7 )2 - 9( x + 4 )2 = 0
<=> x2 - 14x + 49 - 9( x2 + 8x + 16 ) = 0
<=> x2 - 14x + 49 - 9x2 - 72x - 144 = 0
<=> -8x2 - 86x - 95 = 0
<=> -8x2 - 10x - 76x - 95 = 0
<=> -8x( x + 5/4 ) - 76( x + 5/4 ) = 0
<=> ( x + 5/4 )( -8x - 76 ) = 0
<=> \(\orbr{\begin{cases}x+\frac{5}{4}=0\\-8x-76=0\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=-\frac{5}{4}\\x=-\frac{19}{2}\end{cases}}\)
c) ( 2x + 1 )2 + ( 4x - 1 )( x + 5 ) = 36
<=> 4x2 + 4x + 1 + 4x2 + 19x - 5 = 36
<=> 8x2 + 23x - 4 - 36 = 0
<=> 8x2 + 23x - 40 = 0
=> Vô nghiệm ( lớp 8 chưa học nghiệm vô tỉ nghen ) :))
Bài 2.
a) x2 - 12x + 39 = ( x2 - 12x + 36 ) + 3 = ( x - 6 )2 + 3 ≥ 3 > 0 ∀ x ( đpcm )
b) 17 - 8x + x2 = ( x2 - 8x + 16 ) + 1 = ( x - 4 )2 + 1 ≥ 1 > 0 ∀ x ( đpcm )
c) -x2 + 6x - 11 = -( x2 - 6x + 9 ) - 2 = -( x - 3 )2 - 2 ≤ -2 < 0 ∀ x ( đpcm )
d) -x2 + 18x - 83 = -( x2 - 18x + 81 ) - 2 = -( x - 9 )2 - 2 ≤ -2 < 0 ∀ x ( đpcm )
a,2x2+8x+20=2(x2+4x)+20
=2(x2+4x+4)+20-4.2
=2(x+2)2+12
Ta có : 2(x+2)2 \(\ge0với\forall x\)
12 > 0
\(\Rightarrow\)2(x+2)2+12>0 với \(\forall x\)
\(\Rightarrow\)2x2+8x+20>0 với \(\forall\)x
b,x4-3x2+5
=(x4-3x2)+5
=(x4-2.\(\frac{3}{2}\)x2+\(\frac{9}{4}\))+5-\(\frac{9}{4}\)
=(x2-\(\frac{3}{2}\))2+\(\frac{11}{4}\)
Có : (x2-3/2)2\(\ge0với\forall x\)
\(\frac{11}{4}\)>0
\(\Rightarrow\)(x2-\(\frac{3}{2}\))2+\(\frac{11}{4}>0với\forall x\)
\( a)6{x^2} + 7x - 3 < 0\\ \Leftrightarrow 6{x^2} + 9x - 2x - 3 < 0\\ \Leftrightarrow 3x\left( {2x + 3} \right) - \left( {2x + 3} \right) < 0\\ \Leftrightarrow \left( {2x + 3} \right)\left( {3x - 1} \right) < 0\\ \Leftrightarrow \left[ \begin{array}{l} \left\{ \begin{array}{l} 2x + 3 < 0\\ 3x - 1 > 0 \end{array} \right.\\ \left\{ \begin{array}{l} 2x + 3 > 0\\ 3x - 1 < 0 \end{array} \right. \end{array} \right. \Leftrightarrow \left[ \begin{array}{l} \left\{ \begin{array}{l} x < - \dfrac{3}{2}\\ x > \dfrac{1}{3} \end{array} \right.\\ \left\{ \begin{array}{l} x < - \dfrac{3}{2}\\ x < \dfrac{1}{3} \end{array} \right. \end{array} \right. \Leftrightarrow x \in \left( { - \dfrac{3}{2};\dfrac{1}{3}} \right) \)